Experimental Investigation of Animals Prooxidant-Antioxidant Balance During the Induced Generalized Periodontitis and Its Correction by Cryopreserved Human Placenta Extract - Kutsevlyak, V. F.; Grischenko, V. V.; Nikitchenko, J. V. (Problems of Cryobiology and Cryomedicine, 2008)
It has been established that the administration of the cryopreserved human placenta extract to animals with induced generalized periodontitis normalized hyperconcentration of lipidsâ€™ hydroperoxides in blood plasma, content of LPO products and activity ofÂ  ascorbate-induced LPO in liver homogenates. Activity of glutathione-peroxidase in blood plasma and liver increased a lot in comparison with its low level during the pathology development.